The economic theory of illegal goods: a review of the literature - Raffo, Leonardo (Sociedad y Economía, 2011)
This paper makes a critical review of key up to date literature in the developmentof the economic theory of illegal goods, making emphasis in the works about drug trafficking. For that purpose, the paper describes three different kinds of works in the field. The paper states as methodological hypothesis, that the research on drug trafficking networks is relevant, and new models in the field should incorporate the effect of these networks in the analytical frameworks developed until now.